2007
DOI: 10.1634/stemcells.2006-0644
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Stem Cell Antigen-1: Expression, Function, and Enigma

Abstract: Cloned 20 years ago, stem cell antigen-1 (Sca-1) is used extensively to enrich for murine hematopoietic stem cells. The realization that many different stem cell types share conserved biochemical pathways has led to a flood of recent research using Sca-1 as a candidate marker in the search for tissue-resident and cancer stem cells. Although surprisingly little is still known about its biochemical function, the generation and analysis of knockout mice has begun to shed light on the functions of Sca-1 in stem an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
325
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(342 citation statements)
references
References 126 publications
(166 reference statements)
11
325
1
5
Order By: Relevance
“…Previous studies demonstrated that Thy1 expression defines lipofibroblastic or myofibroblastic lineage, 26 while Sca1 is a marker specifying murine mesenchymal and epithelial progenitor cells. 27 Our microarray analyses confirmed that Sca1-single-positive cells (SP) express genes broadly involved in embryonic and tissue morphogenesis, thus indicating their immature origin (Supplemental Table 1), whereas Thy1/Sca1-doublenegative (DN) cells selectively express markers of myofibroblast-committed progenitors (Supplemental Table 2). Notably, the Thy1-positive fractions (composed of Thy1-single positive (Thy1-SP) and Thy1/Sca1 double-positive (DP) cells) represent the majority of MEFs (470%), while Thy1-negative (Sca1-SP and DN) cells are a minority (10-15% each, Figure 1a).…”
Section: Resultssupporting
confidence: 52%
“…Previous studies demonstrated that Thy1 expression defines lipofibroblastic or myofibroblastic lineage, 26 while Sca1 is a marker specifying murine mesenchymal and epithelial progenitor cells. 27 Our microarray analyses confirmed that Sca1-single-positive cells (SP) express genes broadly involved in embryonic and tissue morphogenesis, thus indicating their immature origin (Supplemental Table 1), whereas Thy1/Sca1-doublenegative (DN) cells selectively express markers of myofibroblast-committed progenitors (Supplemental Table 2). Notably, the Thy1-positive fractions (composed of Thy1-single positive (Thy1-SP) and Thy1/Sca1 double-positive (DP) cells) represent the majority of MEFs (470%), while Thy1-negative (Sca1-SP and DN) cells are a minority (10-15% each, Figure 1a).…”
Section: Resultssupporting
confidence: 52%
“…18) Our results showed that large amounts of new CMs were generated in this process. However, we did not investigate the activation of cardiac stem cell-like populations, such as c-kit + , Sca1 + cells.6, [19][20][21] Studies have indicated that neonatal-derived cardiac stem cells have a strong regenerative ability when compared with adult-derived cardiac stem cells. 22,23) In our results, we also noticed that there are large numbers of CMs generated in the normal development of neonatal rat.…”
Section: Discussionmentioning
confidence: 99%
“…While LY6A is frequently used to identify stem and progenitor cells in mouse, LY6A does not have a human homolog, restricting the use of this marker to murine studies (Holmes & Stanford 2007).…”
Section: Ly6amentioning
confidence: 99%